Hubungan Pengetahuan Ibu dengan Pemberian Air Susu Ibu (ASI) Eksklusif pada Bayi Usia 6-12 Bulan di Wilayah Kerja Puskesmas Namrole Kabupaten Buru Selatan - Rahma Tunny (Lembaga Pengembangan Kinerja Dosen, 2024)
According to the United Nations Childrens Funds and the World Health Organization, children should only be breastfed for six months and solid foods given after the child is six months old and continue to be breastfed until the child is two years old. According to WHO, the data on exclusive breastfeeding globally has not increased significantly, namely around 44% of babies aged 0 to 6 months worldwide who received exclusive breastfeeding during the period 2015 to 2018 from 50% of the breastfeeding target (WHO, 2019). Based on the results of interviews with 15 mothers of toddlers, 7 of them said that their children were not given exclusive breast milk due to the lack of milk production so that their babies quickly starved and fussy. 5 mothers of toddlers said that the 3-month-old child could have been given complementary foods for breast milk and 3 other mothers of toddlers said that the heavy workload that made the breastfeeding mother had given MP-ASI from an early age. The general purpose of this study is to see the relationship between maternal knowledge and exclusive breastfeeding in infants aged 6 – 12 months in the working area of the Namrole Health Center, South Buru Regency. This study is an analytical observational research using a cross sectional approach. The results of the chi-square test showed that there was a good relationship between the mother's knowledge about exclusive breastfeeding and exclusive breastfeeding in toddlers with a p value = 0.000. because the p value < 0.005 thus H0 is rejected and Ha is accepted, so there is a good relationship between maternal knowledge and the provision of Exclusive Breastfeeding to toddlers in the working area of the Namrole care center. Knowledge Most of the mothers of babies are in the poor category, which is 56.9%, most of the mothers of babies do not give exclusive breastfeeding, which is 69%, There is a clear relationship between maternal knowledge and exclusive breastfeeding in the work area of the Namrole Health Center.